New Art in Scotland. - Centre for Contemporary Arts, Glasgow; Aberdeen Art Gallery, Aberdeen; Findlay, Judith; Gillick, Liam; Lee, Jane; McArthur, Euan; Sinclair, Ross; White, Nicola; Woods, Alan (Glasgow : CCA Glasgow, 1994)
Berchem, Otto ; Brennan, Sara ; Coley, Nathan ; Currall, Alan ; Dignan, Paul ; Donachie, Jacqueline ; Hollingsworth, Stephen ; Hopkins, Louise ; Kane, Ian ; Lawrence, Dez ; Leighton, Tanya ; McBride, Christina ; Martin, Leigh ; Miller, Andrew ; Morton, Victoria ; Ogg, Kirsty ; Punton, Lesley ; Rhodes, Carel ; Riek, Uwe ; Rousson, Pascal ; Rummelhardt, Sandrine ; Shankie, John ; Shrigley, David ; Smith, Stephanie ; Spark, Judith ; Stevenson, Jeremy ; Stewart, Edward ; Thornhill, James ; Ursitti, Clara ; Wright, Richard
biografie
New Art in Scotland, A CCA exhibition in three parts, Centre for Contemporary Arts, Glasgow, part I 2nd September to 1st October 1994 / part II 7th to 29th October 1994 / part III 4th to 26th November 1994 / An Aberdeen Art Gallery exhibition, 18th January to 11th February 1995
Engels
boek
Keywords: jaren 90; Schotland